PELAKSANAAN PENDIDIKAN POLITIK DI SEKOLAH DALAM MENINGKATKAN KESADARAN POLITIK SISWA - Wildan Nurul Fajar (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2014)
The study was based on concerns about the condition of the political dynamics in Indonesia, particularly in relation to the political awareness of the young generation is minimal gain in political education. This research aims to know how the implementation of political education in schools to increase the political consciousness of students. This study used a qualitative approach and descriptive methods of analysis. Data and information gathering techniques used include the study of documentation, interviews, and observations. The results showed that the school as an important component of education, can basically be used as a medium of political education to inculcate and establish the nation's growing political awareness generation, through various forms of educational programs through both political education, student council and extracurricular activities as well as other forms of activities planned incidental or intending to provide political information to students. Keywords: Civic Education, political education, political awareness